Fraternal Life and Brotherhood in the community life in the Institutes of Consecrated Life and in Associations of Apostolic Life - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2012)
The Code of Canon Law of 1917 regarding the religious person uses the term „community life”. The Code of Canon Law of 1983, however, uses the term „fraternal life in community” (vitam fraternam in communi) and in general norms for all Institutes of consecrated life gives in Canon 602 a definition „fraternity life” . The goal of this article is to explain the meaning of terms used in both Codes and to show the similarities and differences between them. Striking also is the outdated term “community life”. To examine the above - mentioned questions the Author is going back to the beginning of monastic life of cenobites and first monastery founders: St. Pacoima’s, St. Basil, St. Augustine and St. Benedict, who were looking for the sense of community life of monks referred to the First Community in Jerusalem.